(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The Event Management System consists of the planning of the entire event. It is also essential for all the students and professors to see the process of the whole event and have a schedule, time, place, upcoming event, and report of the upcoming activities. The event also has the in charge of the equipment like venues, chairs, lights, sound checks, and other equipment that is used for executing the entire event. It can also help the students to manage their schedules from time to time, the place where the event was taking off, and organize the schedules and time management. It is also essential for the professors to know about upcoming events from other departments. The proper execution of the event will lead to success in executing the event and a faster way to know and organize. In contrast to this, unattentively, students with their schedules are not organized and do not follow the rules and regulations of the event. The users of the Event Management System are the event organizer, event planner, students, and professors; it is limited only to the Bestlink College of the Philippines MV Campus, which aims to execute and organize proper events. It can be seen or posted on the pages, social media sites, and other systems used. It is essential for the event planner to know the request or proposal of the event to start the plan immediately. The cost of event planning will be over a million pesos, which is used for the equipment and tools used to build an event. There are many different things that might happen in an individual’s life, but for them to all be helpful, they must all be planned out and carried out beforehand. A proper event management system can aid in running events. A computerized system is therefore suggested to simplify the event management procedure. The data flow chart aims to graphically represent the movement of the processes and the entity to which they belong to fully comprehend the processes and how they are carried out.